Tu compañía: cortometraje sobre el olvido - Diaz Palomo, Alexandra Giuliana (2023)
The present project consists in the production of a short film of drama genre in web format, directed to all Peruvians, having as main target group young people from 15 to 29 years old, who in their free time surf and consume short films on social networks; and as secondary audience, adults from 35 years old and older who share content with reflective or awareness messages. The short film "Tu Compañía" is a social proposal that highlights the abandonment of the elderly as an anti-value. The audiovisual piece seeks to raise awareness about this frequent practice, and invites the viewer to introspection and awareness about the treatment they have towards the elderly in their environment. Lack of tolerance, rough treatment and senile oblivion are recurring elements in "Tu Compañía", but they are also part of the daily struggle of more than 200 thousand people in our country.